Synergistic Cellulose Hydrolysis Dominated by a Multi-Modular Processive Endoglucanase from Clostridium cellulosi - Yang, Min; Zhang, Kun-Di; Zhang, Pei-Yu; Zhou, Xia; Ma, Xiao-Qing; Li, Fu-Li (Frontiers in Microbiology, 2016)
Recalcitrance of biomass feedstock remains a challenge for microbial conversion of lignocellulose into biofuels and biochemicals. Clostridium cellulosi, one thermophilic bacterial strain dominated in compost, could hydrolyze lignocellulose at elevated temperature by secreting more than 38 glycoside hydrolases belonging to 15 different families. Though one multi-module endoglucanase CcCel9A has been identified from C. cellulosi CS-4-4, mechanism of synergistic degradation of cellulose by various cellulases from strain CS-4-4 remains elusive. In this study, CcCel9A, CcCel9B, and CcCel48A were characterized as processive endoglucanase, non-processive endoglucanase, and exoglucanase, respectively. To understand how they cooperate with each other, we estimated the approximate concentration ratio on the zymogram and optimized it using purified enzymes in vitro. Synergism between individual glycoside hydrolase during cellulose hydrolysis in the mixture was observed. CcCel9A and CcCel48A could degrade cellulose chain from non-reducing ends and reducing ends, respectively, to cello-oligosaccharide. CcCel9B could cut cellulose chain randomly and cello-oligosaccharides with varied length were released. In addition, a β-glucosidase BlgA from Caldicellulosiruptor sp. F32 which could cleave cello-oligosaccharides including G2~G6 to glucose was added to the enzyme mixture to remove the product inhibition of its partners. The combination and ratios of these cellulases were optimized based on the release rate of glucose. Hydrolysis of corn stalk was conducted by a four-component cocktail (CcCel9A:CcCel9B:CcCel48A:BlgA =25:25:10:18), and only glucose was detected as main production by using high-performance anion-exchange chromatography. Processive endoglucanase CcCel9A, dominated in secretome of C. cellulosi, showed good potential in developing cellulase cocktail due to its exquisite cooperation with various cellulases.